(untitled) (Physical Culture and Sport: Scientific Perspective, 2022)
Osteoarthritis is a degenerative disease of the joint, at the beginning of which the articular cartilage is destroyed, and over time, the other elements are involved - bones, nerves, tendons. In the early stages of the disease, the articular cartilage becomes softer, looser, covered with ulcers, gradually it is thinning out, until the complete abrasion, which causes a decrease in the production of synovial fluid. Eventually, excrescences (osteophytes) are created on the heads of the articular bones, and the bones themselves collide with each other. As a result, there is pain in the affected joint; a gradual restriction of its movement is proceeding, until the complete immobilization (ankylosis).